Prospects of anti-inflammatory and urate-lowering therapy of gout: A vector from the past to the future - A. A. Garanin; N. L. Novichkova; N. L. Novichkova (Научно-практическая ревматология, 2022)
The article provides an overview of new and promising drugs aimed at anti-inflammatory and urate-lowering therapy of gout, both already registered and used in clinical practice, and at the stages of implementation or clinical research and demonstrating their high efficacy and safety. Modern views and approaches to the treatment of gout, reflected in foreign and domestic clinical recommendations, are shown. Emphasis is placed on the safety and efficacy of colchicine in gouty arthritis and its cardioprotective properties in comorbid patients suffering from gout in combination with cardiovascular pathology. Information is provided on the effectiveness of new anti-inflammatory drugs for symptomatic therapy of gout: kanakinumab, according to the experience of which our country occupies a leading position in Europe. The efficacy and safety of anakinra allows us to consider the drug as an effective alternative to the traditional approach to antiinflammatory therapy of gout. Rilonacept provides doctors with more potential treatment algorithms in a population of patients with gout that is difficult to treat with traditional treatment. The historical data on the use of adrenocorticotropic hormone as an anti-inflammatory agent in gout are given. Information on reserve, new and promising urate-lowering drugs is provided. The focus is on the safety and efficacy of febuxostat, based on the results of recent large randomized clinical trials. Other drugs that reduce the level of uric acid in the blood plasma are considered: uricosuric agents (probenecid, benzbromarone, sulfinpyrazone, lezinurad, verinurad, dotinurad and archalophenate), xanthine oxidase inhibitors (allopurinol and topiroxostat), pegylated uricase preparations (pegloticase and rasburicase), which can be considered in the future as reserve drugs with the possibility of combined applications with the main means for urate-lowering therapy.